Wettability alteration using functionalized nanoparticles with tailored adhesion to the rock surface for condensate banking mitigation. (16th July 2021) - Sayed, Mohammed; Ow, Hooisweng; Saini, Rajesh; Wang, Zixing
Abstract: Accumulation of liquids near the wellbore in gas reservoirs can result in what is known as liquid banking, causing loss of gas and liquid production. One of the techniques that can be used to mitigate liquid banking is changing the rock wettability from liquid wetting to neutral wetting, allowing the gas to carry the liquid out of the pore space. Double‐functionalized wettability altering silica (SiO2 ) nanoparticles (NPs) were developed. The synthesized NPs were functionalized with both fluoro‐silane (F‐SiO2 NPs) and a charged functional group to enable coupling of the NPs to the substrate. Surfaces treated with F‐SiO2 NPs functionalized with coupling functional group showed superior wear and corrosion resistance in high salinity water compared to single‐functionalized F‐SiO2 NPs. By functionalizing 125 nm SiO2 NPs first with polyethylenimine (PEI‐) or N‐(2‐Aminoethyl)‐3‐aminopropyltrimethoxysilane (DAMO‐) l group followed by fluorination, a water contact angle of 120°and decane contact angle of 70° was achieved. Core flow testing performed under realistic reservoir conditions of pressure and temperature showed that F‐SiO2 NPs coated with PEI achieved a 58% improvement in gas and liquid relative permeability, indicating improvement in the surface repellency to liquids and reduction of the trapped liquid phases inside the pore space of the rocks. The developed double‐functionalized NPs achieved similar performance to the commercially used fluorinated surfactants but using less treatment volume. In addition, these double‐functionalized NPs enable one‐step treatment in the field, which results in simpler operations, shorter treatment time, and better treatment economics.